Bimbingan Belajar Intensif Pasca Pandemi Covid-19 Di Desa Jampang, Bogor - Riska Aulia Oktaviani; Septa Pradiana; Nurliyanti Setiawan (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2022)
The Covid-19 Outbreak has an impact on various aspects of life, especially on the education system. The education system underwent drastic changes, one of which was in the face-to-face learning system where learning that originally ran offline later became online during the pandemic. The government makes various policies, ranging from online learning systems to blended learning methods that can be applied at the elementary school to university level. Changes in the learning system can not be avoided even the impact is felt in almost all educational institutions, from the lowest level to the highest level. The impact of this condition is on the completeness of learning outcomes, so that various efforts are made to overcome these problems, including through door to door learning assistance activities for schools that are isolated and have limited internet networks. This certainly has an impact on changes in people's behavior patterns in everyday life, where the post-Covid-19 pandemic forces everyone to be able to adapt to these changes. The inability to adapt will certainly hinder efforts to achieve educational goals, therefore various innovation steps in the world of education are carried out to adapt to the post-covid-19 situation, one of which is through limited study groups. Nahdlatul Ulama University Indonesia feels the need to reform through the Decree of the Dean of the Faculty of Law and the Faculty of Teacher Training and Education No. 153/LPPM/100.02.14/VI/2022 concerning Real Work Lecture which is a requirement for writing the Final Report, which is part of the form of student service at the Indonesian Nahdlatul Ulama University. Tutoring Assistance (bimbel) aims to provide a pleasant learning atmosphere for the children of Jampang Village, Gunungsindur District, Bogor Regency.